Application of Project Management in Supervised Business Internships - Arias Chaves, Michael (2012)
This article has the objective of presenting the experience gathered in the applicationof supervised business internship projects. These internship programs are part of theBachelor in Business Computer Science program taught at the university of CostaRica (Western Campus). This essay shows the way in which best practices can beapplied when managing projects in instances that combine the academic field and the business sector of Costa Rica.